CtBP1 is essential for epigenetic silencing of μ-opioid receptor genes in the dorsal root ganglion in spinal nerve ligation-induced neuropathic pain - Cheng-Yuan Lai; Ming-Chun Hsieh; Chou-Ming Yeh; Tzer-Bin Lin; Dylan Chou; Hsueh-Hsiao Wang; Kuan-Hung Lin; Jen-Kun Cheng; Po-Sheng Yang; Hsien-Yu Peng (Neurotherapeutics)
Neuropathic pain poses a significant public health challenge, greatly impacting patients' quality of life. Emerging evidence underscores the involvement of epigenetics in dorsal root ganglion (DRG) neurons relevant to pain modulation. C-terminal binding protein 1 (CtBP1) has emerged as a crucial epigenetic transcriptional coregulator. However, the underlying molecular mechanisms of CtBP1-mediated epigenetic regulation in DRG neurons in neuropathic pain remain poorly elucidated. Here, we employed a Sprague‒Dawley rat model of spinal nerve ligation (SNL) to establish a neuropathic pain model. CtBP1 expression in the ipsilateral DRG gradually increased over a three-week period post-SNL. Immunohistochemistry revealed a significant elevation in CtBP1 levels specifically in NeuN-positive neuronal cells in the ipsilateral DRG following SNL. Further characterization demonstrated CtBP1 expression across various subtypes of DRG neurons in SNL rats. Silencing CtBP1 expression with siRNA reversed tactile allodynia in SNL rats and restored both CtBP1 and μ-opioid receptor expression in the DRG in SNL rats. Moreover, Foxp1 was identified to recruit CtBP1 for mediating μ-opioid receptor gene silencing in the DRG in SNL rats. Subsequent investigation unveiled that Foxp1 recruits CtBP1 and associates with HDAC2 to regulate H3K9Ac binding to μ-opioid receptor chromatin regions in the DRG in SNL rats, implicating epigenetic mechanisms in neuropathic pain. Targeting the Foxp1/CtBP1/HDAC2/μ-opioid receptor signaling pathway in the DRG holds promise as a potential therapeutic strategy for managing neuropathic pain.